Towards carbon neutrality in shipping: Impact of European Union's emissions trading system for shipping and China's response - Mao, Zhengkai; Ma, Aidong; Zhang, Zhijun (Ocean & coastal management, 2024)
Global climate change and the rising volume of world trade have made achieving carbon neutrality in shipping essential for meeting the temperature control targets outlined in the Paris Agreement. Consequently, the European Union (EU) has emerged as a strong advocate for carbon neutrality in shipping and is integrating the shipping industry into its Emissions Trading System (ETS) to enable decarbonisation. The EU's unilateral measure is expected to trigger a series of reactions from the global shipping industry. As a result, China, both a major shipping country and developing nation, could potentially attract significant international attention. This study examines the EU ETS for shipping from the perspective of international law. On one hand, the "Kyoto Protocol" does not exclude parties other than the International Maritime Organization (IMO) from taking unilateral measures to address the issue of carbon emissions from shipping. Furthermore, in accordance with the principle of national territorial sovereignty stipulated in the United Nations Convention on the Law of the Sea (UNCLOS), the EU has the right to reduce shipping emissions only within its national jurisdiction. Therefore, the EU has the legal authority to adopt an ETS for shipping, but the effectiveness of its extraterritorial jurisdiction lacks the support of international law. However, since the EU ETS for shipping applies to all ships without distinction, it may potentially violate the principle of Common but Differentiated Responsibilities (CBDR), which could have negative implications for the shipping industry in developing countries. This study focuses on China as the research subject and offers potential solutions for the country when addressing the EU ETS for shipping.